The Marketing and Brand Strategy of Shopee Indonesia in Covid-19 Era - Syiam, Nazilatus; Urfina, Yasyifa Dian; Andaru, Rizka Kurnia (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The use of technology has driven business growth mainly due to the impressive array of information that can be presented remotely. E-commerce is one of the advances in information technology, where a system serves buyers online through computer network media. Technology presents e-commerce as an alternative transactional platform that is accepted by the public as Indonesia is the largest region with the fastest-growing e-commerce in Southeast Asia. The number of e-commerce businesses in Indonesia encourages companies to have attractive marketing strategies in order for consumers to visit e-commerce platforms and ultimately influence consumers to make purchasing decisions. In the middle of the situation with the outbreak of the Covid-19 pandemic, people are required to carry out their activities at home and maintain social distancing by recommendations of the Indonesian government. In supporting the government, Shopee declared itself to be a leading fighter on e-commerce for shopping from home with its campaign program called #ShopeeDariRumah (#ShopeeFromHome). The purpose of this paper is to find out the marketing and brand strategy of online purchase decisions at Shopee during the Covid-19 pandemic era. The results of this study prove that the website, search engine marketing, web banners, social media campaigns, and online purchase decisions have a positive and significant impact on Shopee's marketing and brand image.